IDH mutant gliomas escape natural killer cell immune surveillance by downregulation of NKG2D ligand expression. Issue 10 (1st October 2016) - Zhang, Xiaoran; Rao, Aparana; Sette, Paola; Deibert, Christopher; Pomerantz, Alexander; Kim, Wi Jin; Kohanbash, Gary; Chang, Yigang; Park, Yongseok; Engh, Johnathan; Choi, Jaehyuk; Chan, Timothy; et al.
Abstract: Background: Diffuse gliomas are poorly immunogenic, fatal brain tumors. The basis for insufficient antitumor immunity in diffuse gliomas is unknown. Gain-of-function mutations in isocitrate dehydrogenases (IDH1 and IDH2) promote diffuse glioma formation through epigenetic reprogramming of a number of genes, including immune-related genes. Here, we identify epigenetic dysregulation of natural killer (NK) cell ligand genes as significant contributors to immune escape in glioma. Methods: We analyzed the database of The Cancer Genome Atlas for immune gene expression patterns in IDH mutant or wild-type gliomas and identified differentially expressed immune genes. NKG2D ligand expression levels and NK cell–mediated lysis were measured in IDH mutant and wild-type patient-derived glioma stem cells and genetically engineered astrocytes. Finally, we assessed the impact of hypomethylating agent 5-aza-2′deoxycytodine (decitabine) as a potential NK cell sensitizing agent in IDH mutant cells. Results: IDH mutant glioma stemlike cell lines exhibited significantly lower expression of NKG2D ligands compared with IDH wild-type cells. Consistent with these findings, IDH mutant glioma cells and astrocytes are resistant to NK cell–mediated lysis. Decitabine increases NKG2D ligand expression and restores NK-mediated lysis of IDH mutant cells in an NKG2D-dependent manner. Conclusions: IDH mutant glioma cells acquire resistance to NK cells through epigenetic silencing of NKG2D ligands ULBP1 and ULBP3. Decitabine-mediated hypomethylation restores ULBP1 and ULBP3 expression in IDH mutant glioma cells and may provide a clinically useful method to sensitize IDH mutant gliomas to NK cell–mediated immune surveillance in patients with IDH mutated diffuse gliomas.